Double Nucleus in M83 - Mast, Damian (2006)
M83 is one of the nearest galaxies with enhanced nuclear star formation, and it presents one of the best opportunities to study the kinematics and physical properties of a circumnuclear starburst. Our three-dimensional spectroscopy data in the R band confirm the presence of a secondary nucleus or mass concentration (previously suggested by Thatte and coworkers). We determine the position of this hidden nucleus, which would be more massive than the visible one and was not detected in the optical Hubble Space Telescope images due, probably, to the strong dust extinction. Using a Keplerian approximation, we estimated for the optical nucleus a mass of (5.0 ± 0.8) × 106 M⊙/sin i (r < 1″.5), and for the hidden nucleus, located 4″ ± 1″ to the northwest (position angle of 271° ± 15°) of the optical nucleus, a mass of (1.00 ± 0.08) × 107 M⊙/sin i(r < l″.5). The emission-line ratio map also unveils the presence of a second circumnuclear ring structure, previously discovered by IR imaging (Elmegreen and coworkers). The data allow us to resolve the behavior of the interstellar medium inside the circumnuclear ring and around the binary mass concentration.